Perceived Course of Illness on the Desire for Social Distance From People Suffering From Symptoms of Schizophrenia in India - Salunkhe, Gayatri; Böge, Kerem; Wilker, Tanja; Zieger, Aron; Jena, Sunita; Mungee, Aditya; Ta, Thi Minh Tam; Bajbouj, Malek; Schomerus, Georg; Hahn, Eric (Frontiers in Psychiatry, 2022)
Background: Stigmatization of people with schizophrenia remains a highly relevant topic worldwide, particularly in low- and middle-income countries like India. It is crucial to identify the determinants of the desire for social distance as a proxy for discriminatory behaviour in a socio-cultural context to indicate ways to reduce stigma. This study aims to explore whether the public perception of the perceived course of an illness concerning people with symptoms of schizophrenia has an impact on the desire for social distance. Subjects and Methods: Data collection took place in five cities in India. The sample (N = 447) was stratified for gender, age, and religion. Desire for social distance was sampled based on a self-reported questionnaire using unlabelled vignettes for schizophrenia. First, factor analysis was conducted to identify the main factors underlying the perception of the perceived course of the illness. Subsequently, a regression analysis was conducted to examine the impact of the perception of those prognostic factors on the desire for social distance. Results: Factor analysis revealed two independent factors of the perceived course of an illness: (1) life-long dependency on others and loss of social integration and functioning and (2) positive expectations towards treatment outcome. This second factor was significantly associated with a less desire for social distance toward persons with schizophrenia. Conclusion: The desire for social distance toward people with schizophrenia reduces with the expectation of positive treatment outcomes which underlines the need to raise public mental health awareness and provide psychoeducation for affected people and their family members in India. Help-seeking behaviours can be promoted by directing those needing treatment towards locally available, affordable and credible community-based services rather than facility-based care. Strikingly, lifelong dependency and the inability to socially integrate do not increase the desire for social distance, reflecting the Indian nation’s socio-relational values and insufficiency of public mental health services. This indicates the suitability of systemic therapy approaches in public mental healthcare services to support the family's involvement and family-based interventions in caregiving for mentally ill people across the lifespan.